PENGARUH PROFITABILITAS (ROA), KEBIJAKAN DIVIDEN (DPR), STRUKTUR MODAL (DER), DAN UKURAN PERUSAHAAN (SIZE) TERHADAP NILAI PERUSAHAAN MANUFAKTUR DI BEI PERIODE 2020-2023 - Jefferson Ng, Enrico; Setiady, David; Sitorus, Jessy Safitri; Sanjaya, Ni Made Wulan Sari (Journal Accounting International Mount Hope, 2025)
This study aims to assess the influence of profitability, dividend policy, capital structure, and company size on firm value in the manufacturing sector listed on the Indonesia Stock Exchange (IDX) during 2020–2023. The analysis was conducted using classical assumption tests (normality, multicollinearity, heteroscedasticity) and multiple linear regression, including the coefficient of determination test, the t-test for partial effects, and the F-test for simultaneous effects. The results demonstrate that ROA, DPR, DER, and firm size significantly influence firm value as measured by PBV. The simultaneous test also confirms that all four variables have a significant influence.